KRITIK PLURALISME DALAM MASYARAKAT MAJEMUK ANTARA PEMIKIR DAN MUFASSIR - Helfi, Helfi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2012)
Noisy pluralism in across religion appear impression necessary unification from a variety of religion at hand. Motive equally all religion because religion was sloping carry big contribution appear avariety hardness the members of a religious community. Need appear face religion tolerance, friendly, brotherly, and full lovely. Gamal alÂbanna the sample, interpretate Islam need reconstruction agree with setting community plural. Islam must up to date to following dynamics multi religion. Without platitude again, gamal direct appear alÂQuran prime support when discourse pluralism. All religion in substantive never refuse to correct humanity attitude. Actual understanding religion cruel and unfamiliar need reinterpretate. Neednâ€™d equalize all religion in value because essence any one of religion by right was diffiren. Person equalize substance all religion never tolerance to religios